A PRAGMATIC INVESTIGATION OF LANGUAGE USE IN HIV/ AIDS SOCIAL MANAGEMENT ADVERTISEMENTS IN OGUN STATE, NIGERIA (2012)
Studies on the social management of HIV and AIDS in Nigeria have focused on how awareness about HIV and AIDS has been created through electronic media campaigns and organised interpersonal communication. These studies have not investigated context-constrained language use in the advertisements on the disease despite the wide coverage and potential effectiveness of these advertisements in the public sensitisation about HIV and AIDS. This study, therefore, investigated the pragmatic features of language in selected HIV and AIDS management advertisements with a view to identifying the pragmatic force of the language, its locutions and its intended perlocutionary effects on the audience in Ogun State. Pragmatic and Speech Act theories were adopted for the research. Twenty-five advertisements broadcast to all African countries on both private and government owned television stations by ‘African Broadcast Media’ constituted the data. One hundred and fifty copies of a questionnaire were administered purposively to inhabitants of major cities in Ogun State to determine the perlocutionary effects of the language. Unstructured interviews were also conducted with 50 purposively selected respondents. Data were subjected to content analysis and percentages. Six pragmatic functions manifested in the advertisements: co-opting, projecting, encouraging, embolding, instigating and advising. Co-opting and Projecting were realised through inference (INF), shared situational knowledge (SSK) and relevance (REL) to enlist audience in the mobilisation against HIV and AIDS pandemic. Encouraging and Embolding were projected through SSK and INF to motivate the audience to go for HIV test and speak openly about the virus. Instigating was achieved through indirect speech act to empower the female against discrimination and stigmatisation. Advising was practed through SSK and INF to promote fidelity and safe sex. Eradication of stigmatisation was suggested through vocables pointing to bonding, intimacy, accomplishment and social relations. Unstructured interviews revealed a subtle compulsion created for the audience to check their HIV status through the repetitive use of voiceless bilabial plosive /p/, voiceless alveolar fricative /s/, and voiceless alveolar plosive /t/ which created hypnotic effects. The roll /r/ had a pragmatic effect of reiterating the importance of mutual respect in all relationships. Perlocutionary effect determined through questionnaire indicated that a high number of respondents (74. 6%) affirmed that the language of the advertisements was effective enough to encourage abstinence from premarital and casual sex. Although 53.2% indicated that they were earlier afraid of rejection and 40.5% scared of the outcome of the screening, 73.9% claimed that the language of the advertisements encouraged them to check their HIV status. A total of 87.0% confirmed that they were aware of facts surrounding the contact and spread of the virus having watched the advertisements. Pragmatic functions, locutions and intended perlocutionary effects were exploited by HIV and AIDS management advertisers to sensitise the audience, promote social ties and project into an HIV free African society. Consequently, the pragmatic import of the language proved effective in the management of HIV and AIDS awareness campaign. This import is, therefore, recommended to be considered by Non-governmental Organisations and advertisers in all language-based awareness and control campaigns on the pandemic